IL-1β stimulates ADAMTS9 expression and contributes to preterm prelabor rupture of membranes - Jiasong Cao; Yixin Wang; Qimei Lin; Shuqi Wang; Yongmei Shen; Lei Zhang; Wen Li; Ling Chen; Chunliu Liu; Shihan Yao; Ling Shuai; Xu Chen; et al. (Cell Communication and Signaling)
Abstract Background Preterm prelabor rupture of membranes (pPROM) is a leading cause of neonatal morbidity and mortality. While intra-amniotic infection is a well-established driver of pPROM, the role of sterile intra-amniotic inflammation remains unclear. Recent evidence suggests that interleukin-1 beta (IL-1β) promotes extracellular matrix (ECM) remodeling via downstream effectors, a disintegrin-like and metalloproteinase domain with thrombospondin type 1 motif 9 (ADAMTS9), while protein O-fucosyltransferase 2 (POFUT2) facilitates its O-fucosylation and secretion, amplifying ECM degradation. This study investigates how IL-1β-triggered nuclear factor kappa-B (NF-κB) activation promotes ADAMTS9 and POFUT2 expression, ultimately driving fetal membrane ECM remodeling and weakening in pPROM without signs of intra-amniotic infection. Methods A nested case-control study included maternal serum and fetal membrane samples from 60 pregnant women (34 pPROM, 26 full-term births [FTB]). ELISA measured serum levels of IL-1β and ADAMTS9, and their correlations were analyzed. Mechanistic studies utilized primary human amniotic epithelial cells (hAECs) and fetal membrane-decidua explants with IL-1β treatment. The role of NF-κB was explored using chromatin immunoprecipitation (ChIP) and luciferase assays to assess NF-κB binding to the promoters of ADAMTS9 and POFUT2. A murine model of sterile intra-amniotic inflammation under ultrasound-guided IL-1β injection was used to validate in vitro findings and assess pregnancy outcomes. Results Serum IL-1β and ADAMTS9 levels at 16 weeks of gestation were significantly higher in pPROM cases compared to FTB controls (P < 0.001). A combined model of these biomarkers demonstrated high predictive accuracy for pPROM (AUC = 0.83). Mechanistically, IL-1β activated NF-κB, leading to its binding to the promoters of ADAMTS9 and POFUT2. NF-κB activation promoted ADAMTS9 expression, while POFUT2 enhanced its secretion. Together, these processes drove versican degradation and ECM weakening. Intra-amniotic administration of IL-1β in mice induced fetal membrane weakening, preterm birth, and adverse neonatal outcomes, which were mitigated by the NF-κB inhibitor BAY 11-7082 treatment. Conclusion Maternal serum ADAMTS9 levels at mid-gestation are promising non-invasive biomarkers for pPROM risk stratification. Mechanistically, IL-1β-induced NF-κB activation promotes ADAMTS9 expression and POFUT2-dependent secretion, contributing to fetal membrane weakening. These findings provide new insights into the role and potential therapeutic target for sterile intra-amniotic inflammation in pPROM.